Peningkatan Daya Saing UMKM melalui Financial Technology dan Digital Marketing - Altin, Darus; Wahyudin, Nanang (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The research purpose is to produce a model for increasing the competitiveness of micro, small and medium enterprises (MSMEs) through financial technology and digital marketing in Pangkalpinang City. 60 SMEs were selected as a sample using accidental sampling. Data was collected through observation and interview methods. Data analysis used a mixed method which is a combination of qualitative and quantitative methods, including validity and reliability tests, descriptive analysis, qualitative data analysis, and important performance analysis (IPA). The results show that the performance of MSMEs in implementing financial technology and digital marketing has met expectations, so that MSMEs can improve their service quality dimensions. This research is expected to contribute ideas to Pangkalpinang City government regulations in increasing the competitiveness of MSMEs in the current and future Covid-19 pandemic era.